CASE SERIES ON MDCT ANGIOGRAPHIC FEATURES OF SUPERIOR MESENTERIC ARTERY SYNDROME - Handique, Mridusmita; Jyoti Gogoi, Bhaskar; Sarma Biswas, Siddhartha (Journal of Chitwan Medical College, 2024)
Superior mesenteric artery syndrome is a condition of relatively less incidence where is narrowing of aortomesenteric distance and reduction of aortomesenteric angle. In this case series, we evaluate MDCT findings of cases of this syndrome. The findings of the study are in concordance with results obtained from other authors on this matter.